Poetes moralistes de la Grece - MM. Guigniaut, Patin, Jules Grand (Garnier Freres,Paris, 2021)
A4,grayscale,290 σ. Περιέχει: Hesiod - Theognis - Callinus - Tyrtee - Mimnerme - Solon - Phocylide - Pythagore - Aristote